La genèse architecturale de l’église de la Trinité de Fécamp - Katrin Brockhaus (Tabularia)
The Church of the Holy Trinity in Fécamp, constructed in three major phases between the eleventh and the fourteenth century, stands where Richard I built a collegiate church in 990. This first church is mentioned in several sources, which only allow for a rough reconstruction of the building. They suggest that its western part was a twin-tower west front rather than a genuine Westwerk. The only section known from excavations, the apse appears to be the kernel around which the present building has developped in a sequence of partial reconstructions, each integrating parts of the previous building phase.